2020
DOI: 10.1177/0020764020906433
|View full text |Cite
|
Sign up to set email alerts
|

Personality and attitudes towards people with mental disorders: Preliminary studies results

Abstract: Background: The subject of psychological research all over the world is to understand the factors conditioning relationships between healthy people and people with mental disorders. Authors analysing attitudes towards people with mental disorders emphasize the importance of two types of determinants: personality factors and demographic and social variables. Aim: The aim of the research was to determine the interdependencies between personality traits and attitudes towards people with mental disorders, taking i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(36 reference statements)
1
3
0
Order By: Relevance
“…People who are more emotionally stable usually have a clear personality trait of being calm, relaxed, content with themselves and inclined to be pro-social, caring for the welfare of others, and often less self-interested ( 65–67 ), and it is perhaps this personality trait that makes them less likely to have a prejudiced attitude toward people with TB. Nonetheless, there is no literature on the impact of different personality traits on the level of prejudice among TB patients, but a recent study found that people with a personality bias toward emotional stability and agreeableness held less negative attitudes toward people with mental illness ( 68 ), a finding similar to our study. Brown suggests that using personality traits as a screening tool for healthcare providers may alleviate stigma in TB patients ( 69 ).…”
Section: Discussionsupporting
confidence: 87%
“…People who are more emotionally stable usually have a clear personality trait of being calm, relaxed, content with themselves and inclined to be pro-social, caring for the welfare of others, and often less self-interested ( 65–67 ), and it is perhaps this personality trait that makes them less likely to have a prejudiced attitude toward people with TB. Nonetheless, there is no literature on the impact of different personality traits on the level of prejudice among TB patients, but a recent study found that people with a personality bias toward emotional stability and agreeableness held less negative attitudes toward people with mental illness ( 68 ), a finding similar to our study. Brown suggests that using personality traits as a screening tool for healthcare providers may alleviate stigma in TB patients ( 69 ).…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, previous studies have shown personality traits as serious moderators of attitude. 29 , 77–80 Additionally, earlier study has established that high level of education is a significant predictor of positive attitudes toward PWID 26 , 76 , 81–85 . Further research may include personality traits and level of education to assess the attitudes of an Arab population towards PWID.…”
Section: Limitationsmentioning
confidence: 95%
“…Individuals with higher openness to experiences and agreeableness were inclined to be more open-minded, cooperative, and tactful. These traits help individuals actively interact with and develop friendly attitudes toward individuals with mental disorders (Wolska & Malina, 2020; Yuan et al, 2018). Further investigation should be undertaken to realize which personality traits dominate among nursing students in the design of targeted interventions for those who have negative attitudes toward individuals with mental disorders.…”
Section: Discussionmentioning
confidence: 99%